Sideline help : a sports medicine awareness course - Reid, Matthew G. (Sports Medicine Australia, 2002)
Sports medicine involves a wide range of professionals and as a group these professionals identify medical and health problems relating to sport. This book provides information on preventing injury, first aid for sports injuries, management of specific sports injuries and a safer sport program.